Silencing PsKPP4, a MAP kinase kinase kinase gene, reduces pathogenicity of the stripe rust fungus. (28th September 2018) - Zhu, Xiaoguo; Guo, Jia; He, Fuxin; Zhang, Yang; Tan, Chenglong; Yang, Qian; Huang, Chuanming; Kang, Zhensheng; Guo, Jun
Summary: Many obligately parasitic pathogens absorb nutrients from host plants via specialized infection structures, called haustoria and infection hyphae, to further colonization and growth in the host plant. In the wheat ( Triticum aestivum ) stripe rust fungus, Puccinia striiformis f. sp. tritici ( Pst ), the mitogen‐activated protein kinase kinase (MAPKK) PsFUZ7 is involved in the regulation of haustorium formation and invasive growth. Here, we functionally characterized PsKPP4 of Pst, which is homologous to the yeast MAPKKK STE11. Similar to the silencing of PsFUZ7, the knockdown of PsKPP4 was detected in the vegetative hyphae and haustoria, resulting in the reduced pathogenicity of Pst . Pst urediniospores treated with the STE11 MAPKKK activation inhibitor produced deformed germ tubes. In addition, overexpression of PsKPP4 in fission yeast resulted in the production of fusiform cells and increased tolerance of yeast cells to oxidative stress. The transformation of PsKPP4 into the mst11 mutant of Magnaporthe oryzae partially restored mst11 function. The PsKPP4 protein contains a sterile alpha motif (SAM), Ras association (RA) and kinase domains, similar to its homologues in other fungi. Yeast two‐hybrid assays revealed that the SAM domain is essential for the interaction between PsKPP4 and PsUBC2, a homologue of Ustilago maydis UBC2, known to interact with KPP4, which is associated with the regulation of the Fus3 cascade. Host‐induced gene silencing of PsUBC2 reduced the pathogenicity of Pst slightly, indicating that PsUBC2 also plays a minor role in the regulation of the infection pathway of Pst . These observations indicate that PsKPP4, interacting with PsUBC2, may play an important role in the regulation of infection‐related morphogenesis in Pst .